The function of dialogues in "Aeneas and the lives of others" by Yuri Kosach - Zviahina, H. O.; Pototska, O. I.; Звягіна, Ганна Олександрівна; Потоцька, Олена Іванівна (My University, 2022)
The paper analyses the functions of dialogues in the story «Aeneas and the Lives of Others» by Yuri Kosach. The analysis points out that the national identity becomes one of the central principles of existence for the heroes of the story. The author considers Cohesion and Coherence as a main principle of text organization. The structure of different dialogue models is investigated using several tactics: the variety of the structure of the question / answer, according to the language composition, in terms of vocabulary, morphology and syntax. Thus, this analysis provides important information about various functions of the dialogues, including that of characterizing the heroes, which creates the effect of presence for the reader. The study focuses on the chosen dialogues and the direct speech of characters as spokespersons of the author's quest for the merger of diverse points of view into a single idea with the discourse of the art.
Keywords: functionality; insertion; national identity; parceling